2008
DOI: 10.1074/jbc.m802631200
|View full text |Cite
|
Sign up to set email alerts
|

Ascidian Sperm Glycosylphosphatidylinositol-anchored CRISP-like Protein as a Binding Partner for an Allorecognizable Sperm Receptor on the Vitelline Coat

Abstract: Although ascidians are hermaphroditic, many species including Halocynthia roretzi are self-sterile. We previously reported that a vitelline coat polymorphic protein HrVC70, consisting of 12 EGF (epidermal growth factor)-like repeats, is a candidate allorecognition protein in H. roretzi, because the isolated HrVC70 shows higher affinity to nonself-sperm than to self-sperm. Here, we show that a sperm 35-kDa glycosylphosphatidylinositol-anchored CRISP (cysteine-rich secretory protein)-like protein HrUrabin in a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
31
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
3

Relationship

5
4

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 31 publications
5
31
0
Order By: Relevance
“…As demonstrated by Sawada and coworkers, ascidian sperm display GPI-anchored Crisp proteins that play a role in mediating self-recognition between sperm and egg so as to prevent self-fertilization (Urayama et al 2008 ;Yamaguchi et al 2011 ). In two different species, H. roretzi and C. intestinalis , a GPI-anchored Urabin on the surface of the sperm head binds to a specifi c partner protein in the vitelline coat of the conspecifi c egg (VC70 and VC57 in the two respective species).…”
Section: The Future Of Crisp Protein Relationships In Reproductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As demonstrated by Sawada and coworkers, ascidian sperm display GPI-anchored Crisp proteins that play a role in mediating self-recognition between sperm and egg so as to prevent self-fertilization (Urayama et al 2008 ;Yamaguchi et al 2011 ). In two different species, H. roretzi and C. intestinalis , a GPI-anchored Urabin on the surface of the sperm head binds to a specifi c partner protein in the vitelline coat of the conspecifi c egg (VC70 and VC57 in the two respective species).…”
Section: The Future Of Crisp Protein Relationships In Reproductionmentioning
confidence: 99%
“…4.1 , truncated members typically contain the PR and Hinge domains along with amino-acid sequences at the C-terminal that vary in length from a few residues to several hundred. Members of this class include allurin, the frog sperm chemoattractant whose characteristics are described in the current chapter, insect venom and hookworm antigen proteins (Burnett et al 2008a ), the protease inhibitor-like proteins P115 and P116 (Gibbs et al 2008 ), Ciona intestinalis (Ci) Urabin and Halocynthia roretzi (Hr) Urabin, recently discovered self-identity ligands on ascidian sperm (Urayama et al 2008 ;Yamaguchi et al 2011 ), and the glioma pathogenesis related-like proteins, whose functions are currently unknown, but which include members that are expressed in a testis-specifi c manner (Gibbs et al 2010b ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, we identified a novel protein that strongly interacts with HrVC70 by Far western blotting in the sperm LD-DIM (low density-detergent-insoluble membrane, or so-called lipid rafts) fraction (Urayama et al, 2008). This 35-kDa GPI-anchored glycoprotein, referred to as HrUrabin (Halocynthia roretzi unique lipid rafts-derived binding partner), showed a sequence homology to a CRISP (Cys-rich secretory protein) family, some members of which are known to play roles in fertilization (Yudin et al, 2002;Ellerman et al, 2006;Roberts et al, 2006).…”
Section: Hrurabin a Sperm Binding Partner Of Hrvc70mentioning
confidence: 99%
“…In sea urchin egg, a protein (p350) was isolated as sperm receptor with the egg plasma membrane-vitelline layer complexes (Giusti et al 1997) and another report have shown that EBR1 gene product serves a speciesspecific sperm-interacting protein on the egg vitelline envelope (Kamei and Glabe 2003). In Ascidians (Halocynthia roretzi), the sperm-egg binding is mediated by the molecular interaction between HrUrabin, a glycosylphosphatidylinositol-anchored CRISP (cysteinerich secretory protein)-like protein on the sperm surface and HrVC70 on the polymorphic vitelline coat, but that HrUrabin per se is unlikely to be a direct allorecognition protein (Urayama et al 2008). In Xenopus egg, gp69/64 glycoproteins are two glycoforms in the vitelline envelope and have the same number of N-linked oligosaccharide chains but differ in the extent of O-glycosylation, might serve as sperm receptor (Tian et al 1999).…”
Section: Sperm Receptor/p350mentioning
confidence: 99%